2008
DOI: 10.21608/jfds.2008.124944
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Pumpkin Pulp and Seeds Flours as Nutrient Supplement of Wheat Flour Biscuits

Abstract: Ba an na a* ** * a an nd d M M. .A A.. A Ab bd d E El l-G Ga al le ee el l* * * * F Fo oo od d S Sc ci i.. a an nd d T Te ec ch h.. D De ep pt t. ., , F Fa ac c.. o of f A Ag gr ri ic c. ., , K Ka af fr r E El l-S Sh he ei ik kh h U Un ni iv v. ., , E Eg gy yp pt t.. * ** *F Fo oo od d T Te ec ch h.. R Re es s.. I In ns st ti it tu ut te e, , A Ag gr ri ic c.. R Re es s.. C Ce en nt te er r, , G Gi iz za a, , E Eg gy yp pt t.. B Be es sa aa ar r, , B Ba ad di ia aa a A A.. et al. B Be es sa aa ar r, , B Ba ad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…This might be due Where a=unflavored tea b=funneled tea c=mint tea d=cinnamon tea to the enhanced flavor and enriched texture for end product imparted by the defatted wheat germ flour. This finding is not in agreement with [48] and this could be mainly due to method used for defatting wheat germ flour and perception of acceptance.…”
Section: Sensory Quality Evaluation Of Value Added Productscontrasting
confidence: 57%
“…This might be due Where a=unflavored tea b=funneled tea c=mint tea d=cinnamon tea to the enhanced flavor and enriched texture for end product imparted by the defatted wheat germ flour. This finding is not in agreement with [48] and this could be mainly due to method used for defatting wheat germ flour and perception of acceptance.…”
Section: Sensory Quality Evaluation Of Value Added Productscontrasting
confidence: 57%
“…Resultant data showed that mango seed kernel is a good source of B-carotenes, riboflavin zinc, iron, potassium and calcium. Bessar et al, (2008) Anti nutritional factors (tannins and phytic acid) contained in mango seed kernel were given in table (4). The results showed that although mango seed kernel flour contains considerable amounts of these factors, soaking in water reduces it to the safe level hence the soaking reduces tannins from 4.65 to only 0.65% ( by 4.00%) and phytic acid from 3.80 to 1.93% (by 1.07%) respectively.…”
Section: Chemical Analysesmentioning
confidence: 99%